Endophytic Fusarium oxysporum GW controlling weed and an effective biostimulant for wheat growth - Asim, Syed; Hussain, Anwar; Murad, Waheed; Hamayun, Muhammad; Iqbal, Amjad; Rehman, Hazir; Tawab, Abdul; Irshad, Muhammad; Alataway, Abed; Dewidar, Ahmed Z.; Elansary, Hosam O.; Lee, In-Jung (Frontiers in Plant Science, 2022)
Wheat crop has to compete with several weeds including Avena fatua, a noxious weed that alone is responsible for 30–70% losses in the yield annually. Because of the environmental concerns associated with conventional methods, researchers are on a continuous hunt to find clean alternatives in order to manage weeds. Fungi have shown promising weedicide potential in lab studies. The current study aimed to isolate endophytic fungi from wheat plants which can promote wheat growth and inhibit the growth of common weed, A. fatua. Of several isolates, GW (grayish white) was selected for its promising features, and the strain was identified as Fusarium oxisporum through ITS sequencing technique. This fungus released a number of compounds including Isovitexin, Calycosin, quercetagetin, and dihydroxy-dimethoxyisoflavone that inhibited the growth of A. fatua but did not influence the growth of wheat seedlings. Biomass of this fungus in the soil also reduced growth parameters of the weed and promoted the growth of wheat. For instance, the vigor index of A. fatua seedlings was reduced to only 6% of the control by this endophyte. In contrast, endophyte-associated wheat seedlings showed a higher vigor index than the control. Behind this differential response of the two plants were their contrasting physiological and biochemical status. Lower growth phenotypes of A. fatua seedlings had reduced levels of IAA, GAs, and SA and higher the levels of JA and ABA. Besides, their ROS scavenging ability was also compromised as evident from relatively lower activities of catalase, peroxidase, and ascorbic acid oxidase, as well as higher accumulation of ROS in their leaves. Wheat seedlings response to GW was opposite to the A. fatua. It may be concluded that F. oxysporum GW has the ability to differentially modulate physiology and biochemistry of the two hosts leading to contrasting phenotypic responses.